Enhancement of photocatalytic degradation of Malachite Green using iron doped titanium dioxide loaded on oil palm empty fruit bunch-derived activated carbon. (June 2021) - Loo, Wei Wen; Pang, Yean Ling; Lim, Steven; Wong, Kam Huei; Lai, Chin Wei; Abdullah, Ahmad Zuhairi
Abstract: Iron-doped titanium dioxide loaded on activated carbon (Fe–TiO2 /AC) was successfully synthesized from oil palm empty fruit bunch (OPEFB) using sol-gel method. The properties of the synthesized pure TiO2, Fe-doped TiO2, AC, TiO2 /AC and Fe–TiO2 /AC were examined by various techniques such as field emission scanning electron microscopy (FE-SEM), Fourier-transform infrared spectroscopy (FT-IR), UV–Vis diffuse reflectance spectroscopy (UV–Vis DRS) and nitrogen adsorption-desorption analyses at 77 K. FE-SEM revealed that Fe-doped TiO2 particles were dispersed homogeneously on the AC surface. FT-IR demonstrated high surface hydroxylation after Fe doping on TiO2 and UV–Vis DRS showed that Fe–TiO2 /AC had the lowest band gap energy. Catalytic performance results proved that Fe dopants could restrict the recombination rate of hole and electron pairs, whereas AC support improved the Malachite Green (MG) adsorption sites and active sites of the hybrid catalyst. Photocatalytic degradation of 100 mg/L MG in the presence of 1.0 g/L 15 wt% Fe–TiO2 incorporated with 25 wt% AC, initial solution pH of 4 and 3 mM H2 O2 could achieve the highest removal efficiency of 97% after 45 min light irradiation. This work demonstrates a promising approach to synthesis an inexpensive and efficient Fe–TiO2 /AC for the photocatalytic degradation of organic dye. Graphical abstract: Image 1 Highlights: TiO2, Fe–TiO2, TiO2 /AC and Fe–TiO2 /AC photocatalysts were successfully synthesized. Elucidation of photocatalytic activity based on catalyst's properties. Fe–TiO2 /AC demonstrated the highest photocatalytic activity for Malachite Green. 97% degradation efficiency of 100 mg/L Malachite Green in 45 min.